Abdominal aortic aneurysm and virus infection: A potential causative role for cytomegalovirus infection?. Issue 8 (3rd May 2021) - Jabłońska, Agnieszka; Zagrapan, Branislav; Paradowska, Edyta; Neumayer, Christoph; Eilenberg, Wolf; Brostjan, Christine; Klinger, Markus; Nanobachvili, Josif; Huk, Ihor
Abstract: An abdominal aortic aneurysm (AAA) is a multifactorial disease with a variety of genetic and environmental risk factors, but the exact mechanism of AAA formation and progression is still not well understood. The present study investigated the frequency of cytomegalovirus (CMV), Epstein‐Barr virus (EBV), and papillomavirus types 6 and 11 (HPV6 and HPV11), their impact on clinical manifestations of cardiovascular diseases, and their possible association with inflammation in patients with AAA and healthy volunteers. Genotyping of CMV UL75, EBV LMP‐1, and HPV6, and HPV11 E6 was performed by polymerase chain reaction (PCR), while the viral DNA loads were measured by quantitative real‐time PCR. Cytokine levels were determined by enzyme‐linked immunosorbent assays. The CMV UL75 was detected more frequently in the blood of patients with AAA than in the blood of healthy volunteers (32.7% vs. 6.3%, p  < .0001). Neither EBV LMP‐1 nor HPV6 E6 was found in blood and aortic wall biopsies, while the HPV11 E6 was detected in 36.4% of AAA walls. The CMV infection in patients with AAA was associated with an increased risk of hypertension and coronary artery disease (OR, 9.057; 95% CI, 1.141–71.862; p  = .037; and OR, 2.575; 95% CI, 1.002–6.615; p  = .049, respectively). Additionally, CMV‐infected patients with AAA had higher tumor necrosis factor‐α levels compared with noninfected subjects ( p  = .017). Our findings suggest that CMV infection can stimulate local inflammation in the aorta but is not a direct cause of most abdominal aortic aneurysms.